Operational Efficiency Matter? Financing Diversification and Non-Performing Financing in Indonesian Islamic Rural Banks - Ratih Avisya; Ruspita Rani Pertiwi; Slamet Haryono; Yasni Efyanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Purpose: This study examines the moderating role of the cost-to-income ratio (BOPO) in the relationship between financing diversification (FINDIV) and Non-Performing Financing (NPF) in Indonesian Islamic Rural Banks (BPRS). It aims to determine whether operational efficiency strengthens the effectiveness of financing diversification as a financing risk management strategy. Method: This study employs a quantitative approach using balanced panel data from the quarterly financial reports of 15 BPRS during Q1 2021–Q4 2024, resulting in 240 observations. Panel regression analysis is applied to test the direct and moderating effects among the variables. Results: The findings show that financing diversification has no significant direct effect on NPF. However, operational efficiency, indicated by a lower BOPO ratio, significantly reduces financing risk. BOPO also significantly moderates the relationship between financing diversification and NPF, suggesting that diversification becomes more effective in reducing financing risk when banks operate efficiently. Implications: These findings imply that diversification alone is insufficient to mitigate financing risk; its effectiveness depends on operational efficiency and the bank’s ability to manage portfolio complexity. Originality: This study provides empirical evidence on the moderating role of operational efficiency in the diversification–risk nexus within Indonesian Islamic Rural Banks.